Segmentation of CT head images - Tong, Lee Hau; Ahmad Fauzi, Mohammad Faizal; Ryoichi, Komiya (IEEE Xplore, 2008)
This paper presents the segmentation of the CT head images with different techniques. The system partitions the CT head images into four regions which are skull, calcifications, cerebrospinal fluid (CSF) and brain matter. The method consists of two phases. The first phase is to partition the skull, CSF and brain matter in which we applied the Expectation maximization (EM) algorithm for the segmentation. The second phase is to identify the calcifications where we used thresholding. The system has been tested with a number of real CT head images and has achieved promising results.